Mid-thickness studies of the stress intensity factor in the bulk of bainitic steel - P. Lopez-Crespo; J. Vazquez-Peralta; C. Simpson; T. Buslaps; P. J. Withers (Fracture and Structural Integrity)
The current work aims at estimating the stress intensity factor deep inside the bulk from elastic strain data measured by synchrotron X-ray diffraction. Key features affecting the evaluation of the stress intensity factor are the number of terms in the analytical model describing the crack tip field, the extension and position of the area of interest of the experimental data, the effect of the experimental data collected within the plastic zone and the number of elastic strain data points used. Here a parametric study of these features is presented in terms of their influence for the stress intensity factor determination. It was found that 3 or 4 terms in Williams’ expansion is often sufficient; the data should be collected from across the full range of angles around the crack tip; and the number of points/number of terms should be greater than 40.